2019
DOI: 10.3389/fphys.2019.01298
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Gene Expression Provides New Insights Into Denervation-Induced Skeletal Muscle Atrophy

Abstract: Denervation induces skeletal muscle atrophy, accompanied by complex biochemical and physiological changes, with potentially devastating outcomes even an increased mortality. Currently, however, there remains a paucity of effective strategies to treat skeletal muscle atrophy. Therefore, it is required to understand the molecular mechanisms of skeletal muscle atrophy and formulate new treatment strategies. In this study, we investigated the transcriptional profile of denervated skeletal muscle after peripheral n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 71 publications
7
101
0
Order By: Relevance
“…Recently, we used transcriptome sequencing and bioinformatics methods to systematically analyze the differentially expressed genes involved in denervated muscle atrophy. To the best of our knowledge, it was proposed for the first time that denervated muscle atrophy can be divided into four different transcription stages (Shen et al, 2019). In the oxidative stress stage (0-12 h), oxidative stress occurs early after skeletal muscle denervation, which may be attributed to the loss of contractile function of the target muscle, resulting in decreased blood perfusion in the muscle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we used transcriptome sequencing and bioinformatics methods to systematically analyze the differentially expressed genes involved in denervated muscle atrophy. To the best of our knowledge, it was proposed for the first time that denervated muscle atrophy can be divided into four different transcription stages (Shen et al, 2019). In the oxidative stress stage (0-12 h), oxidative stress occurs early after skeletal muscle denervation, which may be attributed to the loss of contractile function of the target muscle, resulting in decreased blood perfusion in the muscle.…”
Section: Introductionmentioning
confidence: 99%
“…These inflammatory factors cause further inflammation by activating inflammatory response pathways. In the atrophic (3-7 days) and atrophic fibrosis (14-28 days) stages, excessively activated inflammation further initiates the downstream muscle atrophic process, thereby promoting target muscle atrophy and fibrosis (Shen et al, 2019). Overall, oxidative stress, inflammation, atrophy, and atrophic fibrosis sequentially occur following skeletal muscle denervation.…”
Section: Introductionmentioning
confidence: 99%
“…results [16][17][18][19][20]. In many cases, researchers select genes that are upregulated or downregulated more than a specific threshold in a microarray analysis, then perform GO and pathway analysis [20][21][22][23][24][25][26]. However, Yang et al [27] suggested that genes fluctuating less at a significant level could also be of importance for the understanding of specific reactions.…”
Section: Plos Onementioning
confidence: 99%
“…However, Yang et al [27] suggested that genes fluctuating less at a significant level could also be of importance for the understanding of specific reactions. Shen et al [20]…”
Section: Plos Onementioning
confidence: 99%
“…Damage to nerve endings promoted by PNI leads to the disuse of the skeletal muscle innervated by the injured branch [ 15 ]. Therefore, ischemic and inflammatory processes are involved, resulting in the emergence of oxidative stress (OS) [ 15 , 16 ]. Once the peripheral nerve suffers damage, there is accumulation of pro-oxidant substances; simultaneously, the levels of endogenous antioxidants are insufficient to maintain resistance to oxidative damage [ 15 ].…”
Section: Introductionmentioning
confidence: 99%